Models for Recording Age in 1692-1851 Canada: The Political-Cognitive Functions of Census Statistics - Beaud, Jean-Pierre; Prévost, Jean-Guy (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1994)
ABSTRACTAs a number of recent studies have emphasized, it is relevant to examine official statistics not just merely to assess the accuracy of historical data, but also in their own right, as political-cognitive devices which, by providing a standard to measure things, allow for an agreement regarding their objective existence and, therefore, the possibility to act upon them. In this paper, we focus on the different manners according to which, prior to the modern census era, ages of respondents were classified. Four different models emerge from this analysis, which in each case can be related to a specific political and social context.